Counting, Measuring And The Semantics Of Classifiers - Susan Rothstein (Baltic International Yearbook of Cognition, Logic and Communication, 2010)
This paper makes two central claims. The first is that there is an intimate and non-trivial relation between the mass/count distinction on the one hand and the measure/individuation distinction on the other: a (if not the) defining property of mass nouns is that they denote sets of entities which can be measured, while count nouns denote sets of entities which can be counted. Crucially, this is a difference in grammatical perspective and not in ontological status. The second claim is that the mass/count distinction between two types of nominals has its direct correlate at the level of classifier phrases: classifier phrases like two bottles of wine are ambiguous between a counting, or individuating, reading and a measure reading. On the counting reading, this phrase has count semantics, on the measure reading it has mass semantics.